KONTRIBUSI KOMPENSASI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI DI DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN AGAM - Nika Saputra; Rizki Afri Mulia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
This study aims to provide evidence that: (1) To see the contribution of compensation to the job satisfaction of Agam Regency Education and Culture Department employees. (2) To see the contribution of work motivation to the job satisfaction of Agam Regency Education and Culture Office employees. (3) To see the contribution of compensation and work motivation together to the job satisfaction of Agam Regency Education and Culture Department employees. Data collection is done by survey method with questionnaire. the auditor Data analysis techniques used in this study are descriptive and quantitative analysis. The data collected is primary and secondary data that can be classified as independent variables and dependent variables. Work Compensation and Motivation (contribution variables), and Employee Job Satisfaction in the Agam Regency Education and Culture Office (contributed variable). Hypothesis testing in this study uses multiple linear regression test. Based on the results of the study note that: (1) There is a positive and significant contribution between compensation for Employee Job Satisfaction in the Agam District Office of Education and Culture. (2) There is a positive and significant contribution between work motivation on Employee Job Satisfaction in Agam Regency's Office of Education and Culture. (3) There is a positive contribution between compensation and work motivation together to Employee Job Satisfaction in Agam Regency's Office of Education and Culture.